Critical thinking in second language learning: Students’ attitudes and beliefs - Lailiyah, Malikhatul; Wediyantoro, Prilla Lukis (International Journal of Language Education, 2021)
Researches revealed that critical thinking is a solely appraised learning outcome in higher education. However, the study related to students’ perceptions on critical thinking in online learning is not greatly expanded. This study explored students’ attitudes and beliefs of critical thinking within asynchronous learning environments. The participants of this study were English as a Foreign Language (EFL) students in one of the universities in Malang. To obtain the data, a set of questionnaires is distributed through google form and analyzed to describe the learners’ perception. Besides, to draw supplementary information, a form of deep interviews with six students were conducted. The finding indicated that even though the analysis of the questionnaire showed positive attitudes toward critical thinking skills, there were multifaced understanding what critical thinking are.